Phenotypic trend, breeding value and heritability of biometric traits in Marwari horses - MEHTA, SHARAT CHANDRA; TALLURI, THIRUMALA RAO; LEGHA, RAMAVATAR; PAL, YASH; TRIPATHI, BHUPENDRA NATH (The Indian Journal of Animal Sciences, 2021)
Analysis of phenotypic trend and estimation of inbreeding coefficient, breeding value and heritability of biometric traits was carried out for a total of 226 Marwari horses. The pedigree construct divided the entire population of 226 horses into 6 tiers spanning over a period of 30 years. The inbreeding coefficient of the herd was estimated to be 0.0017. The average height at withers, body length, heart girth and body weight of Marwari horses was 150.15±0.04 cm, 151.44±0.06 cm; 170.02±0.19 cm and 371.34±0.52 kg, respectively with non-significant effect of sex, tier and interaction of sex and tier. The Best Linear Unbiased Prediction (BLUP) estimate of breeding value for the height at withers (150.45 cm), body length (151.97 cm), heart girth (169.73 cm) and body weight (366.3 kg) for Marwari horses was -0.059 cm, -0.079 cm, 0.096 cm and 3.526 kg, respectively. The effect of sex and interaction of sex and tiers was non-significant but that of tier on the estimated breeding value for body weight was significant indicating that body weight received favour in breeding programme. The heritability of height at withers, body length, heart girth and body weight has been estimated to be 0.396±0.586, 0.370±0.777, 0.507±1.95 and 0.597±0.612, respectively. Negligible inbreeding and constant phenotype over decades indicated that the Marwari herd has been bred to maintain enough genetic variation and hence it can be the most reliable source of the stallions and mares for propagation and conservation of this legendry breed of horse which is getting diluted and declining at a faster rate.